Nurturing Entrepreneurial Aspirations: The Impact of Perceived Desirability, Feasibility, Action Propensity, and Entrepreneurship Education among University Students - Siahaan, Juniarty; Goenawan, Verrell Alexander (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
The purpose of this research is to examine and analyze the influence of Perceived Desirability, Perceived Feasibility, Propensity to Act, and Entrepreneurship Education on Entrepreneurial Intention. This study adopts a quantitative approach through a survey method. The population of this research consists of all active students in the Faculty of Economics and Business (FEB) at Universitas Pelita Harapan (UPH) who are enrolled in the management program. The sample selection method employed is purposive sampling, with a sample size of 121 respondents. The data analysis tool used in this research is PLS-SEM. The findings reveal that Perceived Desirability, Perceived Feasibility, Propensity to Act, and Entrepreneurship Education have a significant impact on Entrepreneurial Intention. The study model's R-square score is 0.781, placing it in the substantial category for its ability to predict entrepreneurial intention. This R-square value is higher than the previous research's value of 0.611, suggesting that this research model can be further developed to predict entrepreneurial intention within the context of UPH students.